Bioavailability of calcium in an enriched postbiotic system compared to calcium citrate in healthy postmenopausal females; A randomized, double-blind, comparator-controlled, crossover study - Friling, Marina; Haber, Adi; Furman-Assaf, Sharon; Israel, David; Harari, Gil; Evans, Malkanthi; Crowley, David C.; Ouwehand, Arthur C.; Ivanir, Eran (Frontiers in Nutrition, 2023)
Bioavailability of calcium is an important consideration when designing supplements for achieving adequate calcium intake, mainly in high-risk, and aged populations. Alternative supplementation strategies may be able to circumvent absorption issues commonly seen with calcium supplements. The objective of this study was to assess the bioavailability of a single serving of two calcium formulations vs. comparator product in healthy postmenopausal women. A total of 24 participants between 45 to 65 years were enrolled in a randomized, double-blind, 3-phase, crossover study, with a 7-day washout period between phases. The bioavailability of calcium from calcium-carrying Saccharomyces cerevisiae (Ca-SC) or calcium-carrying Lactobacillus (Ca-LAB) in the form of postbiotic products versus calcium citrate, a conventional salt-based calcium supplement, was determined. Each product provided 630 mg of calcium and 400 IU of vitamin D3. After a 14-hour (overnight) fast followed by a single dose of product with a standard low-calcium breakfast, both serum and urine calcium concentrations were assessed for up to 8 and 24 hours, respectively. Ca-LAB resulted in greater calcium bioavailability, demonstrated by significantly higher area under the curve and peak concentration both in blood and urine, and total calcium mass excreted in urine. The bioavailability of calcium was similar for Ca-SC and calcium citrate except for the peak concentration value that was significantly higher for calcium citrate. Both Ca-LAB and Ca-SC were well tolerated with no significant difference in adverse events between the products during the study. These findings suggest that calcium in an enriched postbiotic system is associated with equivalent to higher levels of bioavailability as compared to calcium citrate.